Tenascin expression in endomyocardial biopsy specimens in patients with dilated cardiomyopathy: distribution along margin of fibrotic lesions. Issue 3 (March 1996) - Tamura, A.; Kusachi, S.; Nogami, K.; Yamanishi, A.; Kajikawa, Y.; Hirohata, S.; Tsuji, T.
Abstract : OBJECTIVE: To examine the hypothesis that tenascin, an extracellular matrix glycoprotein, contributes to fibrotic changes in dilated cardiomyopathy. METHODS: The localisation of tenascin in biopsy specimens of the hearts obtained from eight patients with dilated cardiomyopathy was examined using staining by the avidin-biotin-peroxidase complex method. RESULTS: (1) Perimysium and endomysium. Although positive staining for tenascin was observed in the enlarged perimysium and endomysium in all patients, moderately intense staining was characteristically observed near the replacement fibrotic lesions. In the narrow perimysium and endomysium of the myocardium not containing replacement fibrotic lesions, tenascin was not present, as in the control specimens. (2) Replacement fibrotic lesions. Non-homogeneous positive staining for tenascin was detected in all replacement fibrotic lesions examined. Intense tenascin deposition was observed in the peripheral portion of the replacement fibrotic lesions. The tenascin staining observed in the small replacement fibrotic lesions was more intense than that in the large lesions. CONCLUSIONS: Tenascin contributes to the development of the fibrotic changes seen in the dilated cardiomyopathic heart. Its characteristic location, specifically the distribution along the margin of the fibrosis, suggests that fibrotic change is a continuous process in hearts with dilated cardiomyopathy.